Mobile wireless tracker by using bluetooth and smartphone / Mohamad Faris Omar - Omar, Mohamad Faris (2014)
Mobile wireless tracker can find and locate lost personal belongings by using Bluetooth technology and Android smartphone. Many people had weird experience to lost and found their items at random places with unexplainable reasons and this will lead to major frustration when people urgently need the items such as keys, wallet and any personal belongings. An Android application is used as a tracker that provides information to help user to track a Bluegiga BLEl 12 Bluetooth Smart module. The application will be designed by using App Inventor for Android developed by Google and Massachusetts Institute of Technology (MIT) whereas the Bluetooth module will be programmed by using BGScript developed by Bluegiga Technologies and the module powered by a 3 V coin cell battery. CC Debugger by Texas Instruments is used to program a system on chip microcontroller that came onboard in the BLEl 12 module for programming purpose. This system have been tested within a range of normal house and worked perfectly but not effective for long distance purpose due to Bluetooth limitations. By using wireless approach, the lost rate of personal belonging would be decrease remarkably. With the advantage of the new generation of Bluetooth which is Bluetooth 4.0 range from 10 meters up to 100 meters and with the aid of Android apps the lost items will be found effortlessly in no time and consume much less power and successfully guide the user to get back the lost item.